2017
DOI: 10.1016/j.dsr2.2016.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of deep-sea fishes of the Easter Island Ecoregion

Abstract: The Easter Island Ecoregion is in the center of the South Pacific gyre and experiences ultra-oligotrophic conditions that could make it highly susceptible to global change and anthropogenic activities, so it is imperative that these regions are characterized and studied so that conservation and sustainable management strategies can be developed. From the few studies from the region, we know that the coastal areas are relatively depauperate and have relatively high rates of endemism. Here, we present a brief re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 30 publications
1
35
0
Order By: Relevance
“…Although we cannot confirm with exactitude that our specimens represent to C. cookianus or eventually a new species for science, the visual records from the Campana Archipelago is the first register of the genus Coelorinchus in the inner waters of the central region of the Chilean fjords and channels, and in a comparable shallow depth. Although underwater images sometimes do not allow exact identification at species level, it has been shown that visual observations by means of ROV and similar systems are useful tools to document marine biodiversity where traditional sampling is difficult as on seamounts and other the deep-sea environments (Easton et al 2017). In fact, the yellow soldierfish Myripristis chryseres was detected by means of underwater video at Easter Island , and the first record of black corals attached underneath of rocks in shallow waters to the north of Coquimbo was also gained by using an ROV (Gorny et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we cannot confirm with exactitude that our specimens represent to C. cookianus or eventually a new species for science, the visual records from the Campana Archipelago is the first register of the genus Coelorinchus in the inner waters of the central region of the Chilean fjords and channels, and in a comparable shallow depth. Although underwater images sometimes do not allow exact identification at species level, it has been shown that visual observations by means of ROV and similar systems are useful tools to document marine biodiversity where traditional sampling is difficult as on seamounts and other the deep-sea environments (Easton et al 2017). In fact, the yellow soldierfish Myripristis chryseres was detected by means of underwater video at Easter Island , and the first record of black corals attached underneath of rocks in shallow waters to the north of Coquimbo was also gained by using an ROV (Gorny et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Visual documentation by means of ROV is an excellent alternative to investigate benthic communities at locations characterized by extremely irregular bottom structures as raising rocks that inhibit traditional bottom sampling with trawls or dredges and being inaccessible to non-technical divers (Gorny et al 2018). Although images often do not allow exact taxonomic descriptions, within the past years the use of underwater video revealed numerous first records, including registers of new species of fishes and invertebrates from seamounts, oceanic islands and the continental coast of Chile (Friedlander et al 2013;Easton et al 2017;Gorny et al 2018). The general objective of the expedition to the interior waters of the Campana Archipelago, was to investigate the composition of benthic communities in the easternmost part of the KNR and to prove the hypothesis that species composition in the waters around the islands and next to the ocean differ in comparison to channels located much closer to the continent.…”
Section: Introductionmentioning
confidence: 99%
“…The objectives of this study were (i) to describe the echinoderm community at two sites of the EIE and (ii) to explore biogeographic affinities between the observed assemblages and those of the eastern and western South Pacific. Considering the higher degree of endemism reported for the deep communities of the Nazca Ridge and EIE (Friedlander et al 2013;Easton et al 2017) and the distance (i.e., isolation) among potential mesophotic habitats in the EIE, we expect similar high rates of endemism in the EIE mesophotic echinoderms. We hypothesize that fauna will be more similar to that of tropical West Pacific species than those of the Eastern Pacific as found for shallow-water and deep-sea studies of southeast Pacific fauna (Fell 1974;Parin et al 1997).…”
Section: Introductionmentioning
confidence: 88%
“…Due to a combination of the island's remote location, limited habitat diversity, sub-tropical water temperature and relatively young geological age (Randall & Cea, 2010), the fish diversity at Rapa Nui is highly impoverished compared with other Pacific islands, with only 178 fish species currently recorded for the nearshore and epipelagic zones (Easton et al, 2017;Hernández et al, 2015;Randall & Cea, 2010 Prior to the sighting of this species at the Kermadec Islands (29 16 0 S, New Zealand) made in 2014 (Duffy & Ahyong, 2015;Duffy et al, 2017) the southern-most Pacific record for this species was 27 25 0 S off the east Australian coast (Johnson, 2010). Meanwhile, the eastern and northernmost limits of this species range were extended in 2015…”
mentioning
confidence: 99%